Peran MCQ Sebagai Instrumen Evaluasi Dalam Pendidikan Kedokteran - Ayu Shafira, Nyimas Natasha (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2015)
Abstract The Assessment of student learning is part of an educational process. In evaluating the results of the student's education, there are two types of evaluation, namely, the evaluation of formative and summative evaluation. Formative evaluation is used to assess the progress of the learning process, and serve to provide feedback to the student in the learning process. Summative evaluation is used to assess whether the students have achieved the learning objectives and to identify students who are entitled to continue the learning process to the next level, or college students who must repeat the learning process. The educational process in medical education involves the formation of knowledge, skills and attitudes. Therefore,  evaluation process of education must assess three components above. One evaluation instrument used to assess student knowledge in medical education is a Multiple Choice Question (MCQ). MCQ that is used should be a well-constructed MCQ, so that, the MCQ might capable in assessing knowledge, comprehension, application and analysis of medical students towards the medical knowledge.   Keywords : Evaluation, MCQ, Medical education